2015
DOI: 10.1002/path.4578
|View full text |Cite
|
Sign up to set email alerts
|

c‐Met identifies a population of matrix metalloproteinase 9‐producing monocytes in peritumoural stroma of hepatocellular carcinoma

Abstract: Macrophages (Mϕ) are prominent components of solid tumours and exhibit distinct phenotypes in different microenvironments. Previously, we found that tumours could alter the normal developmental process of Mϕ to trigger transient activation of monocytes in the peritumoural stroma of human hepatocellular carcinoma (HCC). In the present study, we showed that a fraction of monocytes in the peritumoural stroma, but not in HCC cancer nests, expressed surface c-Met molecules. Monocytes exposed to tumours strongly exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…For example, we previously identified a c‐Met + monocyte population that accumulated in the peri‐tumoural stroma of HCC. These cells could facilitate disease progression by producing large amounts of MMP‐9 after they interacted with environmental HGF . In the present study, we newly defined a population of Mϕ, CD169 + Mϕ, which accumulated in non‐tumour areas of HCC tissues.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, we previously identified a c‐Met + monocyte population that accumulated in the peri‐tumoural stroma of HCC. These cells could facilitate disease progression by producing large amounts of MMP‐9 after they interacted with environmental HGF . In the present study, we newly defined a population of Mϕ, CD169 + Mϕ, which accumulated in non‐tumour areas of HCC tissues.…”
Section: Discussionmentioning
confidence: 92%
“…Mφ are highly plastic, which allows them to interpret the complex and even contradictory signals that can be present in the tumour stroma [13]. Although classically activated Mφ can suppress tumour initiation by acting as both antigen-presenting cells (APCs) and effector cells, tumour-associated Mφ act to facilitate tumour progression via diverse mechanisms [14][15][16][17][18][19][20][21]. For example, our recent studies showed that intra-tumoural interleukin (IL)-10 + Mφ could induce immune tolerance, whereas peri-tumoural PD-L1 + monocytes/Mφ could attenuate anti-tumour immune responses and promote angiogenesis in human hepatocellular carcinoma (HCC) patients [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…These macrophages activated by the tumor microenvironment express tumor necrosis factor α (TNF-α), which induces c-Met-expression on their surface. These macrophages also express MMP-9, which increases the remodeling of the tumor microenvironment of HCC[ 49 ].…”
Section: Microenvironment In Hccmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMC) were isolated from buffy coats acquired from healthy donors using a Ficoll density gradient as previously described [ 13 ]. The monocytes were purified from PBMCs using anti-CD14 magnetic beads (Miltenyi Biotechnology; Surrey, UK) according to the manufacturer's instructions [ 15 ]. CD14 + monocytes were cultured for seven days in DMEM supplemented with 10% AB serum in the presence 15% TSN or TGF-β1 (10 ng/mL; R & D Systems) or in medium alone to obtain TSN-treated Mφs, TGF-β1-treated Mφs or control Mφs (Med).…”
Section: Methodsmentioning
confidence: 99%
“…Macrophages (Mφs) constitute a major component of immune cell infiltrates in nearly all tumors [ 8 9 ]. Studies have demonstrated that they could promote tumor angiogenesis, metastasis and induce T cell differentiation and activation through the production of cytokines [ 10 15 ]. Our group and others have reported that a high number of infiltrating Mφs could be correlated with both favorable and poor prognoses in different tumor types [ 11 19 ].…”
Section: Introductionmentioning
confidence: 99%